2009
DOI: 10.1088/0953-8984/21/35/355402
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of orthorhombic perovskite yttrium manganite, YMnO3

Abstract: The lattice dynamics of yttrium manganite (YMnO(3)) has been investigated by means of a shell model with pair-wise interionic interaction potential. The experimental data of crystal structure and Raman and infrared frequencies compare well with the lattice dynamical calculations. The phonon dispersion curves found along three high symmetry directions and the density of states of YMnO(3) have also been calculated from this model. The computed phonon density of states is used to derive the macroscopic thermodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…It was concluded that YMnO 3 is an improper ferroelectric. Various theoretical and experimental attempts have been made to understand the anomalous properties of YMnO3 as well as to understand the mechanism of phase transitions, multiferroicity, structure and dynamics of the compounds [33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that YMnO 3 is an improper ferroelectric. Various theoretical and experimental attempts have been made to understand the anomalous properties of YMnO3 as well as to understand the mechanism of phase transitions, multiferroicity, structure and dynamics of the compounds [33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al [22] have indicated the presence of strong electron-electron correlations in GaCNi 3 through the specific heat measurements, whereas a weak ferromagnetism has been observed in AlCNi 3 [21]. ZnCNi 3 is a Pauli PM metal [14] and CdCNi 3 is a superconductor with T c = 3.4 K [24].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 gives the total and partial phonon densities of states for h-YMnO 3 , which span the spectral range from 0 to 75 meV. The phonon vibrations due to Y, Mn and O atoms show distinct difference with those from orthorhombic YMnO 3 [4]. Y1 and Y2 atoms contribute to low energy range (716 meV).…”
Section: Lattice Dynamical Calculationmentioning
confidence: 99%
“…Raman and infrared spectra of h-YMnO 3 have been discussed by Iliev et al [2] and phonon modes were also assigned by Zaghrioui et al [3]. Nevertheless, some vibrational properties such as phonon density of state have not been reported and are still elusive compared with orthorhombic YMnO 3 [4].…”
Section: Introductionmentioning
confidence: 96%